A Time Series Analysis of the Factors Driving the Demand for Real Estate in the Metropolitan Region of Maharashtra - Virendra Balon (Journal of Informatics Education and Research, 2024)
The Real Estate industry is a timeless investment and one of the most valuable assets in the world. The residential real estate sector has been growing steadily and has been further boosted by the work-from-home concept due to the COVID-19 pandemic. Demand forecasting is an important aspect of strategy y and business planning for real estate investors, as it provides information about the potential of the sector in the existing and other markets. This allows investors to make informed decisions on pricing, making strategies for growth, and prospective market. The aim of the research is to Identify the variables that affect the housing demand in Maharashtra, and Identify a model for the demand of Middle-Income Group (MIG) housing in Maharashtra. This research focuses on the demand forecasting for residential real estate units in India, with a specific focus on the Mumbai City, Mumbai Suburbs, Thane and Navi Mumbai Pune, Nasik, Nagpur. The study found that there are several factors that affect the demand for housing in Maharashtra. This included income, location, proximity to public transportation, size of apartment etc. The study also found that the demand for MIG housing in Maharashtra is driven by the growth of the urban population, increasing household income, and changing cultural and economic environments. In conclusion, this study provides valuable insights into the demand for residential real estate units in India, with a specific focus on Mumbai Metropolitan Region. The study highlights the importance of demand forecasting in the real estate industry and need for a model for forecasting the demand for MIG housing in Mumbai. The results of the study can be used by government institutions, real estate developers, and investors to make informed decisions and plan for the future of the real estate industry in Mumbai and India.